Dynamics of salt diffusion and yield of three types of goat's milk cheese - Sonja Srbinovska; Tihomir Čizbanovski; Vladimir Džabirski; Sreten Andonov; Bone Palasevski (Mljekarstvo)
This paper studies the dynamics of salt diffusion during the ageing ofthree types of cheese from goat's milk: Mozzarella, White Brined andPecorino. The salt concentration was consistently analyzed at the 72nd hour and on the 5th, 10th, 20th, 40th, 50th, 60th and 90th day of the cheese ageing period. The distribution of salt in the three layers of cheese – inner (I), middle (II) and outer (III) was also studied. The salt equilibration in the cheese mass of Mozzarella occurred on the 15th day, in the White Brined - on the 60th day,whereas in Pecorino the content of salt even on the 90th day was by 1% lower, in the inner layer than in the two other layers of this cheese. The utilization rate of dry matter was 52.17% in Mozzarella, 50.64% in the White Brined and 48.32% in Pecorino. Accordingly, the yield of Mozzarella is 18.13 ±0.43%, of White Brined - 12.50 ±0.37% and the yield of Pecorino is 9.18 ±0.13%.